Pengaruh Maju Mundurnya Revolusi Mental Terhadap Profesionalisme Mahasiswa Akuntansi - Adjie Avinda; Akhnof Tria Kurnilah; Cut Muthia Kesuma Hayati; Rasyidah Mustika (Universitas Negeri Padang, 2019)
This research is motivated by the existence of one of the accounting fields of accounting keprilakuan, where this accounting discusses about the attitude of a person in taking a decision an event. This is in line with the mental revolution proclaimed by Mr. Joko Widodo about Nawa changes to the character of the nation. This change is very dependent on the activity of students in the activities of Higher Education such as Organization. In doing so, it needs professionalism in facing students so that there will be impact in the form of awards in itself such as Achievement Index received in Higher Education. This study aims to determine the percentage of accounting students in organizational participation and self-motivation to the professionalism of accounting students and the influence of organizational activeness and the reasons in building a mental revolution. This research activity has reached 100% target, where population from research from State University in Padang City that is State Polytechnic of Padang, Andalas University, State University of Padang, and UIN Imam Bonjol. This study uses cluster random sampling, ie sampling is done by taking randomly on the respondent but each population must be represented. The number of respondents is 400 respondents. The results of this study indicate that the activity of the organization and the motivation to learn has a significant influence on the Cumulative Achievement Index of accounting students as a form of accounting student professionalism in the face of the reverse of mental revolution.